The crime of aggression : a commentary / edited by Claus Kreß, Stefan Barriga. - Kress, Claus; Barriga, Stefan (Crime of aggression library, 2017)
The 2010 Kampala Amendments to the Rome Statute empowered the International Criminal Court to prosecute the 'supreme crime' under international law: the crime of aggression. This landmark commentary provides the first analysis of the history, theory, legal interpretation and future of the crime of aggression. As well as explaining the positions of the main actors in the negotiations, the authoritative team of leading scholars and practitioners set out exactly how countries have themselves criminalized illegal war-making in domestic law and practice. In light of the anticipated activation of the Court's jurisdiction over this crime in 2017, this work offers, over two volumes, a comprehensive legal analysis of how to understand the material and mental elements of the crime of aggression as defined at Kampala. Alongside The Travaux Préparatoires of the Crime of Aggression (Cambridge, 2011), this commentary provides the definitive resource for anyone concerned with the illegal use of force.